Preventing Foodborne Illness Associated with Clostridium perfringens - Keith R. Schneider; Renée M. Goodrich; Dirk M. Sampath (EDIS)
This is one in a series of facts sheets discussing common foodborne pathogens of interest to food handlers, processors and retailers. This document is FSHN035, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, IFAS, University of Florida. Publication date: April 2003.